The behaviour of sharks in captivity - Hussain, Syed Makhdoom (Indian Journal of Fisheries, 2011)
Six species of sharks, viz. Engomphodus taurus (sand tiger), Ginglymostoma cirratum (nurse shark),Negoprion brtvirostris (lemon sharks), Carcharhinus plumbeus (sand bar), C. limbatus (Pacific blacktip), and C. leucas (bull shark), were selected to understand some patterns of shark's behaviour. Thegeneral behavioural patterns like follows, circles and give ways were commonly noted among all the6 species; however, each species was found to differ from the other. Locomotion in shirk was foundto be a combination of anguilliform and crangidform modes. Swimming speed for 6 sharks was measuredas distance (cm) travelled per second. Black tip sharks showed highest speed while sand tigers werefound to exhibit lowest speed.